Sub-millimeter detection of a Galactic center cool star IRS 7 by ALMA. (9th March 2020) - Tsuboi, Masato; Kitamura, Yoshimi; Tsutsumi, Takahiro; Miyawaki, Ryosuke; Miyoshi, Makoto; Miyazaki, Atsushi
Abstract: IRS 7 is an M red supergiant star which is located at 5^′ ′_.5 north of Sagittarius A^* . We detected firstly the continuum emission at 340\: GHz of IRS 7 using the Atacama Large Millimeter/submillimeter Array (ALMA). The total flux density of IRS 7 is S_ ν =448± 45 μ Jy. The flux density indicates that IRS 7 has a photosphere radius of R=1170± 60 R_, which is roughly consistent with the previous Very Large Telescope Interferometer measurement. We also detected a shell-like feature with a northern extension in the H30α recombination line using ALMA. The electron temperature and electron density of the shell-like structure are estimated to be T^* _e=4650± 500\: K and n_e=(6.1± 0.6)× 10^4\: cm^-3, respectively. The mass loss rate is estimated to be m 1× 10^-4 M_\: yr^-1, which is consistent with a typical mass loss rate of a pulsating red supergiant star with M = 20 –25 M_ . The kinematics of the ionized gas would support the hypothesis that the shell-like structure made by the mass loss of IRS 7 is supersonically traveling in the ambient matter towards the south. The brightened southern half of the structure and the northern extension would be a bow shock and a cometary-like tail structure, respectively.